2018
DOI: 10.17235/reed.2018.5605/2018
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of a population strategy for the treatment of chronic hepatitis C with direct-acting antivirals

Abstract: The high initial cost of antivirals against hepatitis C prompted development of the "Strategic Plan for Tackling Chronic Hepatitis C in the Spanish National Health System". The objective of this study was the economic evaluation of the first two years of its application in Navarre, Spain. The change in the natural history of hepatitis C produced by the sustained virological response (SVR) was compared to an alternative without treatment and modeled with patient-level data. By means of a discrete events simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…Other studies that have analysed the efficiency of DAAs have shown similar results of health outcomes, showing that they are greater than those yielded by previous therapies and that DAA treatment would reduce the costs of the disease, generating savings in the cost of health care and improving long-term health [ 4 , 5 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies that have analysed the efficiency of DAAs have shown similar results of health outcomes, showing that they are greater than those yielded by previous therapies and that DAA treatment would reduce the costs of the disease, generating savings in the cost of health care and improving long-term health [ 4 , 5 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 98%
“…DAA treatment would reduce the costs of the disease, generating savings in the cost of health care and improving long-term health [4,5,38,39].…”
Section: Plos Onementioning
confidence: 99%
“…The idea that a treatment may be cost-effective, but cannot be adopted due to its budgetary impact, was raised a few years ago concerning hepatitis C [ 44 ] and has appeared more recently in the field of AD [ 45 ]. In 2015, the evaluation of hepatitis C treatments was summarized paradoxically as “cost-effective but unaffordable” [ 44 , 46 , 47 ]. Over the subsequent years, the reality has been different, most of the millions of patients with hepatitis C in Europe having eventually been treated, and the debate is now focused on its eradication [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the subsequent years, the reality has been different, most of the millions of patients with hepatitis C in Europe having eventually been treated, and the debate is now focused on its eradication [48]. The impossible became possible because the price per patient for the treatments fell from an initial €100,000 [47] to €18,000 [46] and because their added health benefits, specifically, avoiding the progression towards chronic liver disease, were taken into account [49].…”
Section: Discussionmentioning
confidence: 99%
“…A estos pacientes se de-ben sumar los miles de enfermos tratados con regímenes basados en interferón en las últimas dos décadas, lo que probablemente supone cerca de 150.000 pacientes curados (3). Este plan, pionero a nivel mundial, ha permitido poner a España en el foco de los países que más han avanzado para conseguir los objetivos marcados por la OMS para la eliminación de la hepatitis C en el año 2030 (13). Pero pese a esos excelentes datos, se estima que en el ámbito de la población general que acude a la atención primaria hay todavía 76.500 personas virémicas.…”
Section: Introductionunclassified